Physiological adaptations to head-out aquatic exercises with different levels of body immersion - Barbosa, Tiago M. (2011)
The purpose of this study was to compare the physiological adaptations to basic head-out aquatic exercises with different levels of body immersion. Sixteen young and clinically healthy subjects (9 women and 7 men) volunteered to participate in this study. Each subject performed 3 repetitions (on land, immersed to the hip, and immersed to the breast) of the aquatic exercise ‘‘rocking horse’’ for 6 minutes. The rating of perceived effort (RPE), the maximal heart rate achieved during the exercitation (HRmax), the percentage of the maximal theoretical heart rate estimated (%HRmax), the peak of oxygen uptake during the exercise (V˙ O2peak), and the energy expenditure (EE) were evaluated. The RPE was significantly higher when exercising immersed to the hip than on land ( p 0.01) and immersed to the breast ( p 0.03). The HRmax and %HRmax were significantly lower when exercising with immersion to the breast than on land ( p 0.01) and with immersion to the hip ( p 0.01). The V˙ O2peak was significantly different between all conditions. The lower mean value was verified when exercising immersed to the breast, followed by immersion to the hip and on land. The EE was significantly higher when performing aquatic exercises on land than when immersed to the hip ( p 0.02) and the breast ( p 0.01). So, physiological responses when exercising immersed to the hip are higher than when immersed to the breast. The physiological responses when exercising on land are higher than when exercising with immersion to the hip and to the breast.